66.2k views
4 votes
Solve for x if log 9 base x + log 3 base x^2 = 2.5​

User Juanleon
by
4.6k points

1 Answer

3 votes

Not sure if the equation is


\log_9x+\log_3(x^2)=\frac52

or


\log_x9+\log_(x^2)3=\frac52

  • If it's the first one:


9^(\log_9x+\log_3(x^2))=9^(\log_9x)\cdot9^(\log_3(x^2))


9^(\log_9x+\log_3(x^2))=9^(\log_9x)\cdot(3^2)^(\log_3(x^2))


9^(\log_9x+\log_3(x^2))=9^(\log_9x)\cdot3^(2\log_3(x^2))


9^(\log_9x+\log_3(x^2))=9^(\log_9x)\cdot3^(\log_3(x^2)^2)


9^(\log_9x+\log_3(x^2))=9^(\log_9x)\cdot3^(\log_3(x^4))


9^(\log_9x+\log_3(x^2))=x\cdot x^4


9^(\log_9x+\log_3(x^2))=x^5

On the other side of the equation, we'd get


9^(5/2)=(3^2)^(5/2)=3^(2\cdot(5/2))=3^5

Then


x^5=3^5\implies\boxed{x=3}

  • If it's the second one instead, you can use the same strategy as above:


x^{\log_x9+\log_(x^2)3}=x^(\log_x9)\cdot x^{\log_(x^2)3}


x^{\log_x9+\log_(x^2)3}=x^(\log_x9)\cdot\left((x^2)^(1/2)\right)^{\log_(x^2)3}

(Note that this step assume
x>0)


x^{\log_x9+\log_(x^2)3}=x^(\log_x9)\cdot(x^2)^{(1/2)\log_(x^2)3}


x^{\log_x9+\log_(x^2)3}=x^(\log_x9)\cdot(x^2)^{\log_(x^2)\sqrt3}


x^{\log_x9+\log_(x^2)3}=9\sqrt3

Then we get


9\sqrt3=x^(5/2)\implies x=(9\sqrt3)^(2/5)\implies\boxed{x=3}

User Pioto
by
4.8k points